Information Behavior of Managers (IBM) and Strategic Information Use (SIU) in Malaysian Industries - Hussin, Norhayati; Jamaludin, Adnan (International Journal of Engineering and Technology, 2018)
This research examines the Information Behavior of Managers (IBM) and Strategic Information Use (SIU) in Malaysian industries.  A total of 491 were involved in the study and results indicated that the IBM significantly influenced the strategic use of information in Malaysian industries. The results also showed that there were differences of IBM among industries in Malaysia.  The findings of this study create awareness to the Malaysian industries on the importance of IBM.  This study is perhaps one of the first to address IBM in the context of Malaysian industries.